The Economic way of thinking - Shafinah Begum, Abdul Rahim (The International Islamic University Malaysia, 2015)
The tribute by Douglass C. North (a Nobel Prize Winner in Economics Sciences, 1993) in the opening of this book drew my attention to it. Within a mere 405 pages, which is considered moderate by the standard of economics books, the authors have successfully arranged the building blocks of economics in a nutshell. The content is cleverly divided into 16 chapters, beginning with the basic feature of economic theory as all social phenomena emerging from actions and interactions of individuals who are choosing in respect to expected benefits and costs to themselves. Discussions revolve around the emphasis on indivdual choices, economizing process and the pro- market preference, concluding that although facts can be observed, it takes a theory to explain the causes.